Expositor interativo para a comunicação de amostras geológicas do MM Gerdau – Museu das Minas e do Metal - Roberto Vaz; Rui Raposo; Mário Vairinhos (Midas: Museus e Estudos Interdisciplinares)
New technologies are being gradually introduced into museums, allowing the exploration of new ways of interaction and communication with exhibitions. This article focuses on the design and evaluation of a displayer prototype, based on tangible user interfaces, created to explore four geological samples from the collection of MM Gerdau – Museu das Minas e do Metal, in Belo Horizonte, Minas Gerais (Brazil). For the development of this project, a methodology of participatory design was adopted, relying on the collaboration between various professionals from the geosciences, education, communication, design and other areas of expertise. In order to provide an enjoyable user experience to museum visitors, some principles of interaction design were followed. The evaluation phase engaged 23 visitors, 3 of whom were blind. From the test results obtained, it was possible to confirm the viability of this type of tangible media technology in this Museum.